Flexible labor supply models - Olivier Bargain (Institute for the Study of Labor (IZA), 2009)
Discrete-choice models of labor supply have become very popular for ex ante evaluations of policy reforms as they easily account for non-convex budget sets. We test the constraints imposed in practice on these models and suggest a fully flexible model that significantly improves fit.
urn:nbn:de:101:1-2009082139
Keywords: H31; J22; 330; Multinomial logit; labor supply; taxation; Arbeitsangebot; Diskrete Entscheidung; Steuerwirkung; Theorie